(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to identify the concept of religious tourism in Iraq and propose a new mechanism for the work of the tourist residence tax and the extent of its impact on tax revenues, as religious shrines have a positive role in attracting large numbers of visitors and arrivals, and achieve spiritual contact between the individual and his Creator, and the millions of visits witnessed by some cities As in the cities of Najaf, Holy Karbala And the city of Kadhimiya and Baghdad, and the city of Samarra it has a direct impact on the economic, social, educational and cultural sectors, as well as it represents an important resource for hard currency to improve and increase national income while improving the volume of production and employment.- The Central Bureau of Statistics, the General Authority for Taxes, the General Tourism Authority, the Holy Shrines, and related laws and instructions, and the research concluded the need to open a special section for the tourism tax in the General Authority for Taxes and give it great importance if the tourism taxes were implemented, and the selection of qualified and competent cadres capable of success and implementation of the tax Tourist.